Interdisciplinary theology as public theology - J. Wentzel van Huyssteen (Acta Theologica)
In this paper I argue for a revisioning of public theology as interdisciplinary theology. In this way an interdisciplinary space is cleared where the notion of the imago Dei, in theology, and human uniqueness, in the sciences, can be brought into a fruitful integrative dialogue. This opens up the possibility for converging arguments, from both theology and paleoanthropology, that ever since prehistory symbolic behavior in Homo sapiens has always included religious awareness. For theologians, this opens up an interdisciplinary possibility to rethink what human uniqueness may mean for the human person. In this way the notion of the imago Dei could be powerfully redefined as emerging from nature itself. Moreover, the liberating character of the imago Dei at its core reveals an ethics of care, a solidarity for the marginalized, and a powerful thrust towards justice and human rights.